Transformation of Islamic Education Teacher Professionalism through the Metric Concept of Social Entrepreneurship in Malang - Munawir Munawir; Muhammad Sabri Sahrir (Universitas Pesantren Kh abdul Chalim Mojokerto, 2025)
Cultural gaps, normative paradigms, and social stress are problems in the competence of Islamic religious teachers that lead to role nihilism. Role nihilism impacts chaotic socio-economic stagnation. Teacher competence has not affected society because it has focused only on textual teaching and learning processes, rather than on developing local potential as a key competence. MAN 2 Malang has enhanced competence by developing entrepreneur-based social skills. Using a qualitative case study, this research analyzes tactical phenomena to develop the competence of Islamic religious teachers. Data instruments were taken from in-depth interviews with the principal, curriculum chair, and school entrepreneurship section as primary data, and these were analyzed using the Huberman model. The research findings indicate that the initial strategy for transforming competencies involves shifting the mindset by integrating the social environment into learning methods, fostering social habituation in entrepreneurship, and engaging in extracurricular activities based on real-world projects. The development of socio-entrepreneurial competencies is measured through aspects such as independence, paradigm, social ethics, and the products produced. The output of teachers' entrepreneurial competencies can produce products with digital branding. The transformation strategy is implemented by making the product a mandatory requirement for graduation and by forming small groups of students accompanied by Islamic religion teachers. This result is where the competence of Islamic religion teachers integrates professionalism and social entrepreneurship as a form of transformation.